Local high relief at the southern margin of the Andean plateau by 9 Ma: evidence from ignimbritic valley fills and river incision - Montero Lopez, Maria Carolina (2014)
A valley-filling ignimbrite re-exposed through subsequent river incision at the southern margin of the Andean (Puna) plateau preserves pristine geological evidence of pre-late Miocene paleotopography in the northwestern Argentine Andes. Our new 40Ar/39Ar dating of the Las Papas ignimbrites yields a plateau age of 9.24 ± 0.03 Ma, indicating valley relief and orographic-barrier conditions comparable to the present-day. A later infill of Plio- Pleistocene coarse conglomerates has been linked to wetter conditions, but resulted in no additional net incision of the Las Papas valley, considering that the base of the ignimbrite remains unexposed in the valley bottom. Our observations indicate that at least 550 m of local plateau margin relief (and likely >2 km) existed by 9 Ma at the southern Puna margin, which likely increased the efficiency of the orographic barrier to rainfall along the eastern and southeastern flanks of the Puna and caused aridity in the plateau interior.